Methods for producing metal-organic framework extrudates
Patent Information
- Application Number
- JP2022530831
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-11-26
- Filing Date
- 2020-07-27
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-07-27
AI Technical Summary
Existing methods for producing metal-organic framework (MOF) extrudates often compromise the structural integrity and mechanical strength of the material due to high pressure and temperature during extrusion, and conventional binders are often incompatible with MOFs.
The method involves mixing MOF materials with extrusion aids such as liquid, solid, and polymeric aids to reduce pressure during extrusion, maintaining structural integrity and enhancing mechanical strength.
The method produces MOF extrudates with reduced deformation, increased surface area, and improved crushing strength, retaining a significant portion of the original MOF's BET surface area and mechanical properties.
Smart Images

Figure 00000021_0000 
Figure 00000021_0001
Abstract
Description
[Technical Field]
[0001] This disclosure generally relates to metal-organic skeleton ("MOF") extrudes. More specifically, this disclosure relates to a method for manufacturing MOF extrudes that maintains the structural integrity of the MOF material and enhances the mechanical strength of the MOF extruder. [Background technology]
[0002] Materials with large internal surface areas, defined by pores and channels, are primarily attracting attention for applications such as catalysis, absorption and / or adsorption technologies, ion exchange, chromatography, and substance storage and / or uptake.
[0003] Among the various strategies for creating microporous and / or mesoporous active materials, the formation of metal-organic frameworks (MOFs) using metal ions and organic molecular building blocks is particularly advantageous. MOF materials offer many advantages, including (i) the ability to achieve larger pore sizes than currently used zeolites, (ii) a larger internal surface area than currently used porous materials, (iii) the ability to control pore size and / or channel structure over a wide range, and (iv) the ease with which organic framework components on the internal surface can be functionalized.
[0004] MOFs are hybrid materials in which metal ions or clusters coordinate to a multitopic organic linker, self-assembling to form a coordination network. These materials have broad potential applications in various fields, including gas storage, gas separation, catalysis, sensing, and environmental remediation. In many of these applications, molded particles are often used to avoid large pressure drops in the reaction bed or to facilitate material handling. Molding of the material can embody various shapes, such as extruded products, rings, pellets, and spheres. To minimize the generation of fine particles during shipping and use, molded particles must have sufficient mechanical strength to withstand the compressive forces generated by the method conditions and the pressure exerted by the weight of the catalyst layer. However, extrusion molding of materials containing MOFs is a relatively untapped area necessary for the versatile formulation of these novel materials.
[0005] MOFs can be damaged during the extrusion process due to conditions such as high pressure and high temperature. Furthermore, binders are often required to improve the mechanical strength of the extruded material, but many binders are incompatible with MOFs, primarily because there are no interlocking surfaces.
[0006] Therefore, there is a need for a method to manufacture MOF extruders without reducing the structural integrity of the MOF material, and a method to improve the mechanical strength of the MOF extruders. [Overview of the Initiative]
[0007] This disclosure relates to a method for producing metal-organic skeleton extruded products using one or more extrusion aids to reduce pressure during the extrusion process and maintain the structural integrity of the metal-organic skeleton. Furthermore, this method can improve the mechanical strength of the metal-organic skeleton extruded product.
[0008] Provided herein is a method for producing a metal-organic skeleton extruder, comprising the steps of (a) mixing a metal-organic skeleton material with an extrusion aid to form a metal-organic skeleton extrusion mixture; and (b) extruding the metal-organic skeleton mixture in an extruder to produce a metal-organic skeleton extruder, wherein the pressure in the extruder is reduced by about 10% to about 55% compared to the pressure in the extruder when extruding a metal-organic skeleton material without an extrusion aid. As described herein, the extrusion aid may be a liquid extrusion aid, a solid extrusion aid, and / or a polymer extrusion aid. The liquid extrusion aid is a linear C3-C3 extrusion aid. 10 Alkyl alcohols, or branched C3-C3 10 It may be an alkyl alcohol. In embodiments, the liquid extrusion aid is selected from the group consisting of 1-propanol, iso-propanol, 1-butanol, iso-butanol, 1-hexanol, and 1-heptanol. In embodiments, the liquid extrusion aid contains water in the range of about 0.5% to 95% by volume.
[0009] As solid extrusion aids, graphite, magnesium stearate, or saturated or unsaturated C 10+ Examples include organic acids or salts thereof. In embodiments, the solid extrusion aid is mixed with the metal-organic skeletal material in an amount ranging from about 0.5% to about 30% by weight.
[0010] The polymer extrusion aid may be polyvinylamide, polyacrylate, polycarbonate, polyamide, polyester, polyether, polyvinylamine, polyvinyl alcohol, polyvinyl ester, or a combination thereof. In one embodiment, the polymer extrusion aid is polyvinyl alcohol. In one embodiment, the metal-organic skeleton mixture contains about 0.5% to 10% by weight of polyvinyl alcohol. The metal-organic skeleton mixture may also contain polyvinyl acetate and water. In one embodiment, the ratio of polyvinyl acetate to water is about 1:1 to about 1:3.
[0011] Metal-organic skeleton extrudes can be formed into shapes such as rods, ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycombs, or granules. Metal-organic skeleton extrudes produced by this method may have a comparative BET surface area of about 40% to about 100%. In embodiments, the metal-organic skeleton material is HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, MOF-274, or a combination thereof. In embodiments, the metal-organic skeleton material has a pore size of about 2 Å to about 50 Å. Metal-organic skeleton extrudes produced by this method may have a comparative BET surface area of about 40% to about 100%.
[0012] In embodiments, the method further includes a step of aging the metal-organic skeleton extruded at a temperature of about 20°C to about 100°C for a period of about 30 minutes or more. In embodiments, the method further includes a step of activating the metal-organic skeleton extruded at a temperature of about 100°C to about 300°C for about 1 hour or more. In embodiments, the step of extruding the metal-organic skeleton extruded is carried out through a die having a diameter of about 0.01 mm to about 50 mm. In embodiments, the metal-organic skeleton extruded can be washed with any solvent. [Brief explanation of the drawing]
[0013] [Figure 1] This is the powder X-ray diffraction (hereinafter referred to as "PXRD") pattern of the HKUST-1 sample from Example 1, which was extruded using a long-chain alcohol. [Figure 2] The N2 adsorption isotherm of the HKUST-1 sample from Example 1, extruded using a long-chain alcohol, is shown. [Modes for carrying out the invention]
[0014] Before further detailing the extruders and extrusion methods of this disclosure, a list of terms is provided below to help you better understand this disclosure.
[0015] All numerical values in this specification and in the claims are modified with respect to the indicated values by “approximately” or “about,” taking into account experimental errors and variations that can be expected by those skilled in the art.
[0016] Unless otherwise specified, the room temperature is approximately 25°C.
[0017] For the sake of brevity, this specification explicitly discloses only certain ranges. However, just as a range from any lower limit can be combined with any upper limit to describe an unexpressed range, a range from any lower limit can be combined with any other lower limit to describe an unexpressed range. Furthermore, even if not explicitly described, a range includes all points or individual values between its endpoints. Thus, all points or individual values, as their own lower or upper limits, can be combined with other points or individual values or other lower or upper limits to indicate an unexpressed range.
[0018] Where used in this disclosure and claims, the singular forms "a," "an," and "the" include the plural form unless the context clearly indicates otherwise.
[0019] In this specification, the term "and / or" as used in expressions such as "A and / or B" is intended to include "A and B," "A or B," and "A" and "B."
[0020] The term "aqueous medium" refers to a liquid containing 5% or more by volume of water. A suitable aqueous medium may consist of, or essentially consist of, water or a mixture of water and a water-miscible organic solvent.
[0021] The term "extrusion molding" refers to the process of pushing a fluid raw material mixture through a die with a desired cross-section.
[0022] The term "extruded material" refers to the elongated object produced during the extrusion molding process.
[0023] The term "pre-crystallization" means that a material, particularly a metal-organic skeletal material, has been pre-synthesized (pre-formed) and is usually separated from the reaction medium in which it was formed.
[0024] The term "paste" refers to a solvated powder that has a dough-like appearance and viscosity.
[0025] As used herein, the terms “metal-organic skeletal material” and “MOF material” refer to a metal or metalloid and an organic ligand capable of coordinating to the metal or metalloid. In certain embodiments, the MOF coordination network of the organic ligand and the metal (or metalloid) forms a porous three-dimensional structure.
[0026] As used herein, the term "MOF extruded" means an extruded MOF material. An MOF extruded comprises one or more metal-organic skeletal materials treated with at least one extrusion aid, and may further include any solvent and binder, pore-forming agents, lubricants, rheological aids, and other additives such as other materials that contribute to stability (e.g., metal powders).
[0027] In general, metal-organic frameworks (MOFs) are a relatively new type of highly porous material with potential applications in a wide range of fields, including gas storage, gas-liquid separation, isomer separation, waste removal, and catalysis. While zeolites are purely inorganic, MOFs use organic ligands to act as "pillars" bridging metal atoms or groups of metal atoms. Like zeolites, MOFs are materials with micropores. The shape and size of the pores in MOFs can be adjusted by selecting organic ligands and metals. Because MOFs can be modified with organic ligands, they have a diverse range of structures that differ from zeolites overall. Factors that influence the structure of MOFs include, for example, the dentin of the ligands, the size and type of the coordinating groups, the addition or substitution of coordinating groups at a distance or in the vicinity, the size and shape of the ligands, the hydrophobicity or hydrophilicity of the ligands, the selection of metals and / or metal salts, the selection of solvents, and reaction conditions such as temperature and concentration.
[0028] MOFs are synthesized or commercially available as non-solidifying microcrystalline powder materials. Many industrial and commercial products require the molding of powdered MOFs into larger, coherent bodies with specific shapes. Traditionally, when powdered MOFs are solidified into larger bodies by methods such as pelletizing or extrusion, undesirable physical and mechanical properties have often been encountered. Specifically, compressing powdered MOFs can significantly reduce the BET surface area due to the pressure sensitivity of the MOF structure, resulting in relatively low crush strength (compressive strength). Furthermore, incorrect processing conditions can lead to whole- or partial phase transformations of the initial MOF structure, as demonstrated by powder X-ray diffraction and BET surface area analysis. Each of these factors can pose problems in manufacturing MOF extrudes in the form of molded bodies and / or in using these molded bodies in various applications.
[0029] While it is desirable to integrate metal-organic framework (MOF) powder materials into a more cohesive (shaped) body containing the metal-organic framework material ("MOF material"), the properties of MOF materials, particularly their weakness to pressure and shear, can lead to undesirable, often significant, reductions in BET surface area. This can occur, for example, during strong pressure (e.g., about 100 psi to several thousand psi) and shear used to strengthen the powdered MOF, especially during extrusion molding, as at least some of the pores within the MOF structure collapse. The conditions for solidifying the powdered MOF into a molded body can lead to the conversion of the MOF structure, at least partially, and sometimes completely, into another material, such as a different crystalline phase. MOF linkages (e.g., MOF extrudes) can sometimes be problematic due to their low crush strength. For example, low crush strength can generate fine powder, which can be disadvantageous in certain applications.
[0030] Therefore, this disclosure provides a method for producing MOF extruders in which MOF deformation is reduced, the surface area of the MOF is increased, and the crush strength (compressive strength) is increased. This method produces MOF extruders by combining one or more extrusion aids with an MOF material. Useful extrusion aids for this method include one or more liquid extrusion aids, solid extrusion aids, and / or polymer extrusion aids.
[0031] The method for producing MOF extruders according to this disclosure may include stirring a mixture of pre-crystallized MOF powder material (MOF material) and an extrusion aid to form a dough (premix) or paste suitable for extrusion. In some cases, stirring may be performed by malling (grinding). Malling is distinguished from milling by not applying constant pressure and by the small amount of force (energy) involved in mixing. Malling usually does not impart enough energy to the MOF to promote a complete conversion of the MOF structure to another crystalline phase. Some MOFs are unstable even with moderate energy input, and even under the mild malling conditions disclosed herein, slight formation of new crystalline phases may occur.
[0032] The MOF materials disclosed herein can be characterized in terms of their porosity. MOF materials may include micropores, mesopores, macropores, and any combination thereof. In this specification, micropores are defined as having a pore diameter of about 2 nm or less, and mesopores are defined as having a pore diameter of about 2 nm to about 50 nm. Interparticle texture voids may also be present.
[0033] Preferably, the MOF extrudates formed in accordance with the disclosure herein retain at least a substantial majority of the BET surface area of the pre-crystallization metal-organic framework powder materials from which they are formed. Specifically, the metal-organic framework materials within the MOF extrudates may be characterized by a BET surface area of about 50%, 60%, 70%, 80%, 90% or more of the BET surface area of the pre-crystallization metal-organic framework powder materials. Advantageously, and surprisingly, in some instances, the BET surface area of the metal-organic framework linking materials within the extrudates may even be greater than the BET surface area of the pre-crystallization metal-organic framework powder materials. The pelletized samples may exhibit values close to the BET surface area of the metal-organic framework linking materials.
[0034] As described herein, the MOF can be a ZIF (or zeolite imidazolate framework), MIL (or Materials from the Lavoisier Institute), and IRMOF (or Isoreticular Metal Organic Frameworks) alone or in combination with other MOFs. In some embodiments, the MOF can be selected from HKUST-1, MOF-74, MIL-100, ZIF-7, ZIF-8, ZIF-90, UiO-66, UiO-67, MOF-808, or MOF-274.
[0035] The MOF can be prepared, as described hereinafter, via combinations of organic ligands, or combinations of one or more organic ligands with a metal or metalloid. For example, MOF-274 is a combination of Mg 2+ , Mn 2+ , Fe 2+ , Zn 2+ , Ni 2+ .Cu 2+ , Co 2+ or combinations thereof with 4,4'-dihydroxy-(1,1'-biphenyl)-3,3'-dicarboxylic acid. Additionally, MOF-274 can include amines coordinated to the metal sites within its structure.
[0036] As used herein, "isotherm" refers to the adsorption of an adsorbent as a function of concentration while keeping the system temperature constant. In the embodiment, the adsorbent is CO2, and the concentration can be measured as CO2 pressure. As described herein, isotherms can be performed using porous materials and various mathematical models applied to calculate the apparent surface area. S. Brunauer, P.H. Emmett and E. Teller, J.Am.Chem.Soc. 1938, 60, 309-319; K. Walton and R.Q. Snool, J.Am.Chem.Soc. 2007, 129, 8552-8556; I. Langmuir, J.Am.Chem.Soc. 1916, 38, 2221. organic ligand
[0037] As used in this specification, the organic ligand is a monodentate, bidentate, polydentate, or combination thereof. Generally, the organic ligand is capable of coordinating to a metal ion, and in principle, all compounds suitable for such coordination can be used. The organic ligand may contain at least two centers capable of coordinating to the metal ion of a metal salt, or to a metal or metalloid. In some embodiments, the organic ligand comprises i) an alkyl group substructure having 1 to 10 carbon atoms, ii) an aryl group substructure having 1 to 5 aromatic rings, and iii) an alkyl or arylamine substructure consisting of an alkyl group having 1 to 10 carbon atoms or an aryl group having 1 to 5 aromatic rings, wherein the substructure has at least two covalently bonded functional groups "X" where X is capable of coordinating to a metal or metalloid.
[0038] In some embodiments, each X is CO2H, OH, SH, NH2, CN, HCO, CS2H, NO2, SO3H, Si(OH)3, Ge(OH)3, Sn(OH)3, Si(SH)4, Ge(SH)4, Sn(SH)3, PO3H, AsO3H, AsO4H, P(SH)3, As(SH)3, CH(RSH)2, C(RSH)3, CH(RNH2)2, C(RNH2)3, CH(ROH) 2. Independently selected from C(ROH)3, CH(RCN)2, C(RCN)3, CH(SH)2, C(SH)3, CH(NH2)2, C(NH2)2, CH(OH)2, C(OH)3, CH(CN)2, C(CN)3, nitrogen-containing heterocycles, sulfur-containing heterocycles, and combinations thereof (where R is an alkyl group having 1 to 5 carbon atoms, or an aryl group consisting of 1 to 2 phenyl rings).
[0039] In some embodiments, organic ligands include substituted or unsubstituted, mononuclear or polynuclear aromatic di-, tri-, and tetracarboxylic acids, as well as substituted or unsubstituted aromatic di-, tri-, and tetracarboxylic acids containing at least one heteroatom (which may have one or more nuclei).
[0040] In some embodiments, the organic ligands include benzenetricarboxylate (BTC) (one or more isomers), ADC (acetylenedicarboxylate), NDC (naphthalenedicarboxylate) (any isomer), BDC (benzenedicarboxylate) (any isomer), ATC (adamantanetetracarboxylate) (any isomer), BTB (benzenetribenzoate) (any isomer), MTB (methanetetrabenzoate), ATB (adamantanetobenzoate) (any isomer), biphenyl-4,4'-dicarboxylate, benzene-1,3,5-tris(1H-tetrazole), imidazole or its derivatives, or combinations thereof.
[0041] Ligands having polydentate functional groups have a corresponding counter cation, for example, H + na + , K + Mg 2+Ca 2+ Sr 2+ ammonium ions, alkyl-substituted ammonium ions, aryl-substituted ammonium ions, or counter anions, for example F - Cl - ,Br - , I - , - ClO2 - ClO3 - ClO4 - , OH - NO3 - NO2 - SO4 2- , SO3 2- , PO4 3- CO3 2- This may include the following.
[0042] In some embodiments, the organic ligand contains a monodentate functional group. A monodentate functional group is defined as a site attached to a substructure that can form only one bond to a metal ion, which can contain the previously defined organic ligand or amine ligand substructure L. According to this definition, the ligand can contain one or more monodentate functional groups. For example, cyclohexylamine and 4,4'-bipyridine are ligands that contain monodentate functional groups, since each functional group can bond to only one metal ion.
[0043] Therefore, cyclohexylamine is a monofunctional ligand containing a monodentate functional group, and 4,4'-bipyridine is a difunctional ligand containing two monodentate functional groups. Specific examples of ligands with monodentate functional groups include pyridine (a monofunctional ligand), hydroquinone (a difunctional ligand), and 1,3,5-tricyanobenzene (a trifunctional ligand).
[0044] MOF materials can be prepared by blending ligands having monodentate functional groups with ligands having polydentate functional groups in the presence of suitable metal ions and optionally a template agent. Monodentate ligands can also be used as template agents. A template agent may be added to the reaction mixture to occupy the pores in the resulting MOF material. Monodentate ligands and / or template agents may include the following substances and / or derivatives thereof. A. Alkyl or arylamines or phosphines and their corresponding ammonium or phosphonium salts. Alkylamines or phosphines may contain a linear, branched, or cyclic aliphatic group (and their corresponding ammonium salts) having 1 to 20 carbon atoms, and arylamines or phosphines may contain 1 to 5 aromatic rings including heterocycles. Examples of monofunctional amines are methylamine, ethylamine, n-propylamine, iso-propylamine, n-butylamine, sec-butylamine, iso-butylamine, tert-butylamine, n-pentylamine, neo-pentylamine, n-hexylamine, pyrrolidine, 3-pyrroline, piperidine, cyclohexylamine, morpholine, pyridine, pyrrole, aniline, quinoline, isoquinoline, 1-azaphenanthrene, and 8-azaphenanthrene. Examples of difunctional and trifunctional amines include 1,4-diaminocyclohexane, 1,4-diaminobenzene, 4,4'-bipyridyl, imidazole, pyrazine, 1,3,5-triaminocyclohexane, 1,3,5-triazine, and 1,3,5-triaminobenzene. B. Alcohols containing an alkyl or cycloalkyl group with 1 to 20 carbon atoms, or an aryl group containing 1 to 5 phenyl rings. Examples of monofunctional alcohols are methanol, ethanol, n-propanol, iso-propanol, allyl alcohol, n-butanol, iso-butanol, sec-butanol, tert-butanol, n-pentanol, iso-pentanol, sec-pentanol, neopentanol, n-hexanol, cyclohexanol, phenol, benzyl alcohol, and 2-phenylethanol. Examples of difunctional and trifunctional alcohols are 1,4-dihydroxycyclohexane, hydroquinone, catechol, resorcinol, 1,3,5-trihydroxybenzene, and 1,3,5-trihydroxycyclohexane. C. Ethers containing an alkyl or cycloalkyl group with 1 to 20 carbon atoms, or an aryl group with 1 to 5 phenyl rings. Examples of ethers are diethyl ether, furan, and morpholine. D. Thiols containing an alkyl or cycloalkyl group with 1 to 20 carbon atoms, or an aryl group with 1 to 5 phenyl rings. Examples of monofunctional thiols are thiomethane, thioethane, thiopropane, thiocyclohexane, thiophene, benzothiophene, and thiobenzene. Difunctional and trifunctional thiols are 1,4-dithiocyclohexane, 1,4-dithiobenzene, 1,3,5-trithiocyclohexane, and 1,3,5-trithiobenzene. E. Nitriles containing an alkyl or cycloalkyl group with 1 to 20 carbon atoms, or an aryl group with 1 to 5 phenyl rings. Examples of monofunctional nitriles are acetonitrile, propanenitrile, butanenitrile, n-valeronitrile, benzonitrile, and p-tolunitrile. Examples of difunctional and trifunctional nitriles are 1,4-dinitrilocyclohexane, 1,4-dinitrilobenzene, 1,3,5-trinitrocyclohexane, and 1,3,5-trinitrobenzene. F. Inorganic anions from the group consisting of sulfuric acid (sulfate), nitrate, nitrite, sulfurous acid, bisulfite, phosphoric acid, hydrogen phosphate, dihydrogen phosphate, diphosphate, triphosphate, phosphorous acid, chlorine, bromine, iodine, carbonic acid, bicarbonate, thiocyanide, and isonitrile, as well as the corresponding acids and salts of the said inorganic anions. G. Organic acids and their corresponding anions (and salts). Examples of organic acids include alkyl organic acids having 1 to 20 carbon atoms and containing linear, branched, or cyclic aliphatic groups, or aryl organic acids having 1 to 5 aromatic rings, which may contain heterocycles, and their aryl organic anions and salts. H. Other organic and inorganic substances such as ammonia, carbon dioxide, methane, oxygen, ethylene, hexane, benzene, toluene, xylene, chlorobenzene, nitrobenzene, naphthalene, thiophene, pyridine, acetone, 1-2-dichloroethane, methylene hydrochloride, tetrahydrofuran, ethanolamine, triethylamine, or trifluoromethylsulfonic acid.
[0045] Furthermore, the template agent may also contain other aliphatic and aromatic hydrocarbons that do not contain functional groups. In some embodiments, the template agent includes cycloalkanes such as cyclohexane, adamantane, or norbornene, and / or aromatics such as benzene, toluene, or xylene. metal ions
[0046] As described above, MOFs can be synthesized (prepared) by combining metal ions, organic ligands, and optionally, suitable template agents. Suitable metal ions include metals and metalloids with various coordination geometries and oxidation states. In some embodiments, MOFs are prepared using metal ions with distinctly different coordination geometries in combination with ligands having polydentate functional groups and suitable template agents. MOFs can be prepared using metal ions that prefer octahedral coordination, such as cobalt(II), and / or metal ions that prefer tetrahedral coordination, such as zinc(II). MOF materials are prepared together with the counterions of the corresponding metal salts. Mg 2+ Ca 2+ Sr 2+ Ba 2+ , Sc 3+ , Y 3+ Ti 4+ , Zr 4+ , Hf 4+ , V 4+ , V 3+ , V 2+ Nb 3+ Ta 3+ , Cr 3+ Mo 3+ , W 3+ Mn 3+ Mn 2+ Re 3+ Re 2+ Fe 3+ Fe 2+ , Ru 3+ , Ru 2+ Os 3+ Os 2+ Co 3+ Co 2+ , Rh 2+ , Rh + , Ir 2+ , Ir + Ni 2+ Ni + , Pd 2+ , Pd + Pt 2+ Pt + Cu 2+ Cu + Ag + Au + Zn 2+ , Cd2+ , Hg 2+ , Al 3+ , Ga 3+ , In 3+ , Tl 3+ , Si 4+ , Si 2+ , Ge 4+ , Ge 2+ , Sn 4+ , Sn 2+ , Pb 4+ , Pb 2+ , As 5+ , As 3+ , As + , Sb 5+ , Sb 3+ , Sb + , Bi 5+ , Bi 3+ , Bi + , Be 2+ , can be produced using one or more of the metal ions. The term metal ion means ions of both metals and metalloids. In some embodiments, the metal ions suitable for use in the production of the MOF material, together with the counter anions of the corresponding metal salts, , Sc 3+ , Ti 4+ , V 4+ , V 3+ , V 2+ , Cr 3+ , Mo 3+ , Mg 2+ , Mn 3+ , Mn 2+ , Fe 3+ , Fe 2+ , Ru 3+ , Ru 2+ , Os 3+ , Os<000,0115>, Co 3+ , Co 2+ , Rh 2+ , Rh + , Ir 2+ , Ir + , Ni 2+ , Ni + , Pd 2+ , Pd + , Pt 2+ , Pt + , Cu 2+ , Cu + , Ag+ Au + Zn 2+ , Cd 2+ , Al 3+ , Ga 3+ In 3+ , Ge 4+ , Ge 2+ Sn 4+ Sn 2+ Pb 4+ Pb 2+ Sb 5+ Sb 3+ Sb + , Bi 5+ , Bi 3+ , Bi + , and / or Be 2+ , This may include: In some embodiments, metal ions for use in the production of MOF materials are, together with the counterions of the corresponding metal salts, Sc 3+ Ti 4+ , V 4+ , V 3+ , Cr 3+ Mo 3+ Mn 3+ Mn 2+ Fe 3+ Fe 2+ Co 3+ Co 2+ Ni 2+ Ni + Cu 2+ Cu + Ag + Zn 2+ , Cd 2+ , Al 3+ Sn 4+ Sn 2+ , Bi 5+ , Bi 3+ , and / or Bi + , Includes. In some embodiments, metal ions for use in the production of MOF materials are, together with the counterions of the corresponding metal salts, Mg 2+ Mn 3+ Mn 2+ Fe 3+ Fe 2+ Co 3+ Co2+ Ni 2+ Ni + Cu 2+ Cu + Pt 2+ Ag + , and Zn 2+ , It is selected from the group consisting of the following. Manufacturing of MOF materials
[0047] The synthesis of rigid and stable MOF materials can be carried out under very mild reaction conditions. Often, reagents are prepared in aqueous or non-aqueous solutions, and the synthesis reaction temperature is between 0°C and 100°C (in an open beaker). In other cases, the solution reaction takes place in a sealed container at a temperature between 25°C and 300°C. In either case, large single crystals or microcrystalline microporous solids are formed.
[0048] In the preparation of MOF materials, reactants can be added in a molar ratio of 1:10 to 10:1 between metal ions and polydentate functional group-containing ligands. In some embodiments, the ratio of metal ions to ligands containing polydentate functional groups is 1:3 to 3:1, for example, 1:2 to 2:1. The amount of template agent may not affect the production of MOF materials, and in fact, the template agent can be used as the solvent in which the reaction takes place, depending on the circumstances. Therefore, a large amount of template agent can be used without hindering the reaction or the preparation of MOF materials. Furthermore, when ligands containing monodentate functional groups and ligands containing polydentate functional groups are used in combination with metal ions, the ligands containing monodentate functional groups may be used in excess. In certain circumstances, ligands containing monodentate functional groups can be used as the solvent in which the reaction takes place. Furthermore, in certain circumstances, the template agent and the ligand containing monodentate functional groups may be the same. An example of a template agent that contains a monovalent functional group is pyridine.
[0049] The preparation of MOF materials may be carried out in either an aqueous or non-aqueous system. The solvent may be polar or nonpolar and may be a template agent or any ligand containing a monodentate functional group. Examples of non-aqueous solvents include n-alkanes such as pentane, hexane, benzene, toluene, xylene, chlorobenzene, nitrobenzene, cyanobenzene, aniline, naphthalene, and naphtha, n-alcohols such as methanol, ethanol, and n-propanol, and isopropanol. Examples include isopropanol, acetone, 1,2-dichloroethane, methylene chloride, chloroform, carbon tetrachloride, tetrahydrofuran, dimethylformamide, dimethyl sulfoxide, thiophene, pyridine, ethanolamine, triethylamine, and ethylenediamine. The appropriate solvent can be selected based on the solubility of the starting reactants, and the choice of solvent may not be important in obtaining the MOF material.
[0050] To facilitate the formation of large single crystals of microporous materials suitable for single-crystal X-ray structure analysis, solution reactions may be carried out in the presence of viscous materials such as polymer additives. Specific additives include polyethylene oxide, polymethyl methacrylic acid, silica gel, agar, oils and fats, and collagen, which can help achieve high yields and pure crystalline products. Growing large single crystals of microporous materials allows for clear characterization of the microporous framework. Large single crystals of microporous materials can be useful in magnetic and electronic sensing applications.
[0051] This specification provides a method for producing MOF extruded products using the above-mentioned MOF material. In this method, the MOF material and an extrusion aid are mixed to form an MOF extrusion mixture. Then, this MOF extrusion mixture is extruded to form an MOF extruded product.
[0052] To form MOF extruders, the extruder may be a ram extruder (also called an extruder press) or a screw extruder. In a ram extruder, the MOF material is pushed through a die by a mechanically or hydraulically operated plunger or piston. In a screw extruder, the MOF material is transported from the feed point to the die by a rotating screw, such as an auger. After formation, the MOF extruders may be dried and calcined as described herein.
[0053] Generally, an extruder is a machine used to produce extruded products having a defined cross-sectional shape. An extruder typically includes a hopper for supplying raw materials, a barrel or other confinement into which the raw materials are bound, and a die having a die opening into which the extruded product is formed. The material, forcibly homogenized by temperature, pressure, and shear within the barrel, is passed through a die opening having various cross-sectional shapes. The shape of MOF extruded products can be rods or ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycomb bodies, granules, or similar shapes.
[0054] As described herein, the MOF material used in this method is combined with one or more extrusion aids and optionally with additives that can modify various physical properties of the extruded material. The additives can be combined with the MOF material before or during extrusion. Exemplary extruders and extrusion processes for other types of extruded materials are described in further detail in U.S. Patent No. 4,441,990 (column 12, lines 23-19, line 64) (incorporated herein by reference) and U.S. Patent No. 6,517,807 (column 5, lines 35-50) (incorporated herein by reference).
[0055] Extrusion methods according to this disclosure may include mixing or co-supplying the MOF material with one or more extrusion aids that enable extrusion of the MOF at lower operating pressures and / or improve the mechanical properties of the MOF extruder. The extrusion process may or may not be carried out with any solvent or solvent mixture. In some embodiments, the MOF extruder exhibits substantially the same or improved physical qualities as the original MOF material, exhibiting surface area and mechanical strength suitable for commercial use. Extrusion aids include liquid extrusion aids, solid extrusion aids, and polymer aids that reduce the pressure during MOF extrusion and preserve or improve structural properties such as crystallinity and porosity of the starting MOF material.
[0056] As used in this method and as shown in the following examples, extrusion aids are used to reduce pressure during the extrusion process and are also useful for maintaining specific operating pressures within limits in large extruders. In embodiments, the extrusion aid may include material remaining in the MOF extruder, as well as material that does not remain in the MOF extruder and is removed after extrusion by washing and / or maturation. Extrusion aids can also improve the mechanical stability of a wide range of MOF materials having various metal nodes, pore structures, and crystallite sizes. As a result, this method can be applied to various types of MOF crystals and extrusion aids. Overall, extrusion aids such as those used in this method provide reduced MOF deformation during extrusion, increased surface area of the MOF extruder, and increased crush strength of the MOF extruder. Extrusion aid
[0057] As described herein, the MOF extruders of this disclosure comprise at least one MOF material and at least one extrusion aid. As provided herein, the extrusion aid may be a liquid extrusion aid, a solid extrusion aid, and / or a polymer extrusion aid. In this method, the extrusion aid plays a role in reducing pressure in the extruder and during the extrusion method, thereby minimizing or eliminating mechanical deformation and / or reduction of surface area of the MOF material. The extrusion aid is used in this method to enable the production of MOF extruders that may be damaged by extrusion. Liquid extrusion aid
[0058] As provided herein, the liquid extrusion aid comprises water and linear and branched alkyl alcohols having an alkyl chain having at least two carbon atoms. In embodiments, the liquid extrusion aid includes C3-C3 alcohols such as 1-propanol, iso-propanol, 1-butanol, iso-butanol, 1-hexanol, and 1-heptanol. 10 Alkyl alcohols may be included. In this embodiment, C 10 Liquid extrusion aids with a larger number of carbon atoms can be used when the compound remains in liquid form and can be combined with MOF materials.
[0059] A method for producing MOF extruders includes the steps of mixing MOF material with water alone and / or with one or more extrusion aids to form an MOF extrusion mixture. Optionally, a solvent may be used instead of water. In embodiments, the MOF extrusion mixture may contain water in a volume percentage (vol%) ranging from about 0.5 vol% to 95 vol%. Solid extrusion aid
[0060] Examples of solid extrusion aids include graphite, montmorillonite, kaolin, bentonite, halloysite, dickite, nacrite, and anorthite clays. Graphite has a specific surface area of 0. G (For example, about 3-8m) 2 / g or more), particle size D 50 It can be characterized by being approximately 45-150 μm or less. D 50 This means that 50% of the particles are smaller than the indicated value. For use in this method, graphite includes natural graphite, synthetic graphite, and graphite modifiers containing expanded graphite, graphite intercalation compounds, graphite nanofibers (GNF) or carbon nanotubes (CNT), and mixtures thereof. Graphite is available from many manufacturers and suppliers with a variety of properties.
[0061] In the present invention, the solid extrusion aid is C 10+Solid organic acids and their salts, such as magnesium stearate, may be included. Furthermore, the solid extrusion aid may contain saturated and unsaturated C 10+ It contains organic acids.
[0062] Solid extrusion aids are combined with MOF materials in weight percentages (wt%) ranging from approximately 0.5 wt% to 30 wt%, 1 wt% to 40 wt%, and 5 wt% to 30 wt%. Polymer extrusion aid
[0063] The present method for producing MOF extruders may include a step of mixing MOF material with one or more polymer extrusion aids. The polymer extrusion aids may be polar polymers and include homopolymers and copolymers such as esters, amides, acetates, and anhydrides, for example, C2-C2 polymers such as ethylene and / or propylene and / or butene. 20 Examples include copolymers of olefins with acetates, anhydrides, esters, alcohols, and / or one or more polar monomers such as acrylics. Further examples of polymer extrusion aids include polyesters, polyamides, ethylene vinyl acetate copolymers, polyvinyl chloride, polyvinyl alcohol (PVA), polyvinylamines or their derivatives. In embodiments, the polymer extrusion aid comprises polyvinyl alcohol or its derivatives, such as polyvinyl alcohol, polyvinyl acetate, polyvinyl butyrate, or polypropionate.
[0064] In one embodiment, the polymer extrusion aid is a polymer blend of two or more polymers. The polymer extrusion aid may include a polymer mixture in which the first polymer is present in weight percent (W%) of the polymer mixture in the range of about 10% to about 99% by weight, for example, 20% to 95% by weight, 30% to 90% by weight, 40% to 90% by weight, or 50% to 90% by weight, with the remainder being the second polymer or a combination of polymers. In an embodiment, the polymer extrusion aid comprises a polymer blend of polyvinyl alcohol and polyvinyl acetate.
[0065] The present disclosure provides a method for producing MOF extruders, comprising the step of mixing an MOF material with one or more polymer extrusion aids to form an MOF extrusion mixture. In embodiments, the MOF extrusion mixture may contain at least a polymer or polymer blend. The MOF material and polymer extrusion aids may be mixed with any solvent, and optionally one or more polymer extrusion aids. In embodiments, the extrusion mixture may contain a polyvinyl acetate to water ratio in the range of 1:1 to 1:3. Blend of extrusion aids
[0066] Extrusion aid blends ("extrusion aid blends") can be produced by mixing one or more polymers (as described above), by connecting reactors in series to create reactor blends, or by producing multiple types of polymers using one or more catalysts in the same reactor. In the case of blends, two or more extrusion aids can be mixed together before being put into the extruder, or mixed in the extruder before being mixed with the MOF material.
[0067] Extrusion aid blends can be formed using any suitable apparatus and method, for example, by dry blending the individual components and then melt-mixing them in a mixer, or by directly mixing the components together in a single-screw or twin-screw extruder, which may include a Banbury mixer, Haake mixer, Brabender internal mixer, or a compounding extruder and side-arm extruder used directly downstream of the polymerization method, and may include a blend of resin powder or pellets in the hopper of a film extruder. Any additives
[0068] Furthermore, additives can be incorporated into MOF extrudes. Examples of such additives include fillers; antioxidants (e.g., hindered phenols such as IRGANOX® 1010 or IRGANOX® 1076, available from Ciba-Geigy); phosphates (e.g., IRGAFOS® 168, available from Ciba-Geigy); anti-flocculants; adhesives such as polybutene, terpene resins, aliphatic and aromatic hydrocarbon resins, alkali metals and glycerol stearates, and hydrogenated rosin; UV stabilizers; heat stabilizers; anti-blocking agents; release agents; antistatic agents; pigments; colorants; dyes; waxes; silica; fillers; and talc.
[0069] Other optional additives include silica derived from by-products such as precipitated silica or fly ash, such as silica-alumina, silica-calcium particles, and fumed silica. In certain embodiments, the silica is particulate matter with an average particle size of 10 μm or less, for example, 5 μm or less, or 1 μm or less. In one embodiment, the silica is amorphous silica.
[0070] Other additives include inorganic compounds such as titanium dioxide, hydrated titanium oxide, hydrated alumina or alumina derivatives, mixtures of silicon and aluminum compounds, silicon compounds, clay minerals, alkoxysilanes, and amphiphilic substances. Additives may also include compounds suitable for bonding powdered materials such as oxides of silicon, aluminum, boron, phosphorus, zirconium, and titanium. Furthermore, magnesium oxides and beryllium oxides can be included as additives. In addition, tetraalkoxysilanes can be used as additives, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, similar tetraalkoxytitanium, tetraalkoxyzirconium compounds, trimethoxy-, triethoxy-, tripropoxy-, and tributoxy-aluminum.
[0071] The additives can have concentrations between 0% by weight and about 40% by weight, and between about 20% by weight and about 40% by weight, based on the total weight of one or more extrusion aids. Manufacturing method for MOF extruded products
[0072] As described herein, the method includes the step of mixing MOF material with an extrusion aid and optionally other additives to form an extrusion mixture. The method also includes the step of extruding the extrusion mixture to form an MOF extruded product. The method for producing MOF extruded products of this disclosure includes the production of granules, i.e., molded products. Thus, in certain embodiments, the MOF extruded product is formed and molded or granulated to form granules or shaped products.
[0073] The method may further include a step of washing the extruder with an arbitrary solvent, and a step of drying and / or calcining the MOF extruder. Examples of arbitrary solvents include water, alcohols, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof. In certain embodiments, the arbitrary solvent is selected from the group consisting of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, and combinations thereof. In certain embodiments, the arbitrary solvent is water. In certain embodiments, the arbitrary solvent is a mixture of two or more solvents. Any solvent can be used to wash the MOF material and / or MOF extruder at different stages of the method.
[0074] The mixing process can be carried out in any suitable way, for example, by dry blending the individual components and then melt-mixing them in a mixer, or by directly mixing the components together in a mixer, including Banbury mixers, Haacke mixers, Brabender internal mixers, etc. Other examples include high-shear mixers, drum mixers, or single-screw or twin-screw extruders (which may include compound extruders and side-arm extruders used directly downstream of the polymerization method, and which may include mixing of the MOF material in powder or pellet form in the extruder hopper). In certain embodiments, the mixing and extrusion processes are simultaneous, such as when the MOF material and extrusion aid are mixed and extruded in an extruder. Alternatively, the MOF material and extrusion aid may be mixed with any solvent and then extruded.
[0075] MOF material and extrusion aid can be pre-mixed as dry materials. The order of adding the components (MOF material, extrusion aid, and any solvent) depends on the material being added. The order of adding the extrusion aid, MOF material, and any solvent is not specified, but the optimal order is determined by the type of mixer used.
[0076] As described herein, the mixing process can be achieved by material processing or unit operation methods. Agitation can be used for mixing in the liquid phase, while kneading and / or extrusion can be used when the mixture is paste-like. Solid components and powders can be mixed in a mixer. Depending on the state of the parts used, atomizers, sprayers, diffusers, and nebulizers may also be used. For paste-like or powder-like MOF materials, static mixers, planetary mixers, mixers with rotating containers, pan mixers, pug mills, shearing disc mixers, centrifugal mixers, sand mills, trough kneaders, internal mixers, internal kneaders, and continuous kneaders are desirable. The mixing process only needs to be sufficient to achieve molding or extrusion, such as when mixing and extrusion are performed simultaneously.
[0077] Furthermore, the mixing process can be carried out continuously or in batches. When mixing is done in batches, this method can be performed using a mixer equipped with a Z-arm, a mixer equipped with a cam, or another type of mixer such as a planetary mixer. The mixing process can provide a homogeneous mixture of powder components. Mixing can be carried out for 5 to 60 minutes, for example, 10 to 50 minutes, and it is desirable that the maximum mixing time be 60 minutes or less. The rotation speed of the mixer arm may be 10 to 75 rpm, for example, 25 to 50 rpm.
[0078] The MOF extrusion mixture may contain 1% to 99% by weight of MOF material, e.g., 5% to 99% by weight, 7% to 99% by weight, or 10% to 95% by weight; 1% to 99% by weight of extrusion aids (including any additives), e.g., 1% to 90% by weight, 1% to 50% by weight, or 1% to 20% by weight; and optionally 0% to 20% by weight of solvent, e.g., 1% to 15% by weight, 1% to 10% by weight, or 1% to 7% by weight. The weight percentages are expressed with respect to the total amount of compounds and / or powders in the mixture, where the sum of the respective amounts of compounds and powders in the mixture equals 100%. In some embodiments, the MOF extrusion mixture contains about 20% to about 70% by weight of solids, based on the total weight of the mixture.
[0079] In this method, the extrusion process can be carried out using a single-screw or twin-screw ram extruder. If the process of preparing the MOF material is carried out continuously with the extrusion, mixing may be linked to the extrusion in one or more devices. According to this embodiment, the extrusion of the MOF extruded mixture, also called "kneaded paste," may be carried out either by direct extrusion at the end of a twin-screw continuous mixer, for example, or by connecting one or more batch mixers to the extruder. The shape of the die that gives shape to the extruded material can be selected from any suitable die, such as cylindrical, multi-lobed, grooved, or slitted.
[0080] Extrusion may be affected by the amount of extrusion aids and any solvents added, and can be adjusted to obtain a mixture or paste that is not fluid and does not dry out excessively, enabling extrusion under appropriate pressure conditions depending on the extruder used. In some embodiments, extrusion is carried out at extrusion pressures of about 1 MPa or more, for example, about 0.1 MPa to about 20 MPa, about 2 MPa to about 15 MPa, or about 3 MPa to about 10 MPa.
[0081] MOF extrudes include pelletized materials, and the product may be in the form of MOF extrudes or MOF extruded pellets. However, this does not preclude the use of the obtained MOF material in devices that round or spheroidize surfaces, such as tumblers.
[0082] MOF extruders may have a diameter of about 1 to about 10 mm, for example, about 1.5 to about 5 mm. In some embodiments, the mixture is extruded through a die having a diameter of about 0.01 mm to about 50 mm, for example, about 0.05 mm to about 40 mm, about 0.1 mm to about 20 mm, about 0.2 mm to about 10 mm, or about 0.5 mm to about 7 mm. Such extrusion apparatus is described, for example, in Ullmann's *Enzylopadie der Technischen Chemie*, 4th edition, Vol. 2, p. 295, 1972. In addition to using an extruder, an extrusion press may also be used.
[0083] For MOF extrudes, aging may be optionally performed, such as drying or solidifying the MOF extrudes. Aging may include temperatures of about 0°C to about 300°C, for example, about 20°C to about 200°C, or about 20°C to about 150°C. Aging may be performed for periods of about 1 minute to about 72 hours, for example, about 30 minutes to about 72 hours, about 1 hour to about 48 hours, or about 1 hour to about 24 hours. In some embodiments, aging may be carried out in air or humidified air with a relative humidity of 20% to 100%, for example, 70% to 100%. Treatment with a humidified gas may allow hydration of the material and may be beneficial for solidifying certain extrusion aids. In some embodiments, aging may be carried out in dehumidified air or an inert gas, such as air with a relative humidity of 0% to 10%, or 0% to 5%.
[0084] MOF extrudes or mature MOF extrudes may optionally be activated. Activation can be carried out at temperatures of approximately 50°C to approximately 500°C, for example, approximately 100°C to approximately 300°C. Activation may be carried out for approximately 1 hour ("h") to approximately 6 hours, for example, approximately 1 hour to approximately 4 hours. Activation can help remove solvents used to facilitate the extrusion of the mixture. Activation can be carried out in air, an inert gas, or a gas mixture containing oxygen. Furthermore, activation can be carried out under reduced or increased pressure conditions, such as in a vacuum or at a pressure higher than atmospheric pressure. In certain embodiments, the extrudes are calcined in dry air or air with different levels of humidity, or they are heat-treated in the presence of a gas mixture containing an inert gas such as nitrogen and / or oxygen. In certain embodiments, the gas mixture used may contain 5% or more by volume of oxygen, for example, 10% or more by volume. In alternative embodiments, the gas mixture contains only an inert gas, and does not contain or substantially contains no oxygen. The calcination temperature may be from approximately 50°C to the decomposition temperature of the MOF material. Properties of MEF extruders
[0085] MOF extrudes produced by this method may have bulk crush strengths of approximately 0.2 lb-force to approximately 80 lb-force, for example, approximately 0.4 lb-force to approximately 50 lb-force, approximately 1 lb-force to approximately 20 lb-force, or approximately 4 lb-force to approximately 15 lb-force. Crushing strength may also depend on the size of the extruder, and the extruder may have a shape that extends to approximately 1 mm or more in each direction within space. Bulk crush strength is measured by a standardized test (ASTM D7084-04).
[0086] The MOF extruded material produced by this method has a BET surface area (measured using ASTM D3663) of approximately 50 m². 2 / g ~ approx. 4,000m 2 / g, approx. 50m 2 / g ~ approx. 3,000m 2 / g, approx. 50m 2 / g ~ approx. 2,000m 2 / g, about 100m 2 / g ~ approx. 1,800m 2 / g, about 100m 2 / g ~ approx. 1,700m 2 / g, about 100m 2 / g ~ approx. 1,600m 2 / g, about 100m 2 / g ~ approx. 1,550m 2 / g, about 100m 2 / g ~ approx. 1,500m 2 / g, about 100m 2 / g ~ approx. 1,450m 2 / g, about 100m 2 / g ~ approx. 1,400m 2 / g, about 100m 2 / g ~ approx. 1,300m 2 / g, about 100m 2 / g ~ approx. 1,250m 2 / g, about 100m 2 / g ~ approx. 1,200m 2 / g, about 100m 2 / g ~ approx. 1,150m 2 / g, about 100m 2 / g ~ approx. 1,100m 2 / g, about 100m 2 / g ~ approx. 1,050m2 / g, approximately 100m 2 / g~approximately 1,000m 2 / g, approximately 100m 2 / g~approximately 900m 2 / g, approximately 100m 2 / g~approximately 850m 2 / g, approximately 100m 2 / g~approximately 800m 2 / g, approximately 100m 2 / g~approximately 700m 2 / g, approximately 100m 2 / g~approximately 600m 2 / g, approximately 100m 2 / g~approximately 550m 2 / g, approximately 100m 2 / g~approximately 500m 2 / g, approximately 100m 2 / g~approximately 450m 2 / g, approximately 100m 2 / g~approximately 400m 2 / g, approximately 100m 2 / g~approximately 300m 2 / g, approximately 100m 2 / g~approximately 200m 2 / g, approximately 300m 2 / g~approximately 1,800m 2 / g, approximately 300m 2 / g~approximately 1,700m 2 / g, approximately 300m 2 / g~approximately 1,600m 2 / g, approximately 300m 2 / g~approximately 1,550m 2 / g, approximately 300m 2 / g~approximately 1,500m 2 / g, approximately 300m 2 / g~approximately 1,450m 2 / g, approximately 300m 2 / g~approximately 1,400m 2 / g, approximately 300m 2 / g~approximately 1,300m 2 / g, approximately 300m 2 / g~approximately 1,250m 2 / g, approximately 300m 2 / g~approximately 1,200m 2 / g, approximately 300m 2 / g~approximately 1,150m 2 / g, approx. 300m 2 / g ~ approx. 1,100m 2 / g, approx. 300m 2 / g ~ approx. 1,050m 2 / g, approx. 300m 2 / g ~ approx. 1,000m 2 / g, approx. 300m 2 / g ~ approx. 900m 2 / g, approx. 300m 2 / g~about 850m 2 / g, approx. 300m 2 / g~about 800m 2 / g, approx. 300m 2 / g~about 700m 2 / g, approx. 300m 2 / g~about 600m 2 / g, approx. 300m 2 / g ~ approx. 550m 2 / g, approx. 300m 2 / g~about 500m 2 / g, approx. 300m 2 / g~about 450m 2 / g, or about 300m 2 / g~about 400m 2 It may have a value of / g. In particular, MOF extruded material is approximately 300m 2 / g ~ approx. 4,000m 2 / g, for example, about 500m 2 / g ~ approx. 1,600m 2 It may have a total BET surface area of / g.
[0087] Furthermore, the MOF extruded by this method may have a comparative BET surface area of approximately 30% to 100% of the unprocessed (raw material) MOF, for example, approximately 50% to 95%, or approximately 70% to 90% (measured using ASTM D3663). The comparative BET surface area is defined as the value obtained by dividing the BET surface area of the MOF extruded by the BET surface area of the MOF material. For example, if an MOF extruded is prepared using HKUST-1 and the MOF extruded is 1292m² 2 If the BET surface area is / g, then 1292m 2 / g is 1615m 2 Since it is 80% of / g (calculated BET surface area for HKUST-1), the MOF extruded material will have a comparative BET surface area of 80%.
[0088] The MOF extruded material produced by this method has a pore volume (measured using ASTM D3663) of approximately 0 cm³. 3 / g ~ approx. 1.6cm 3 / g, approx. 0.2cm 2 / g ~ approx. 1.6cm 2 / g, 6cm 3 / g, approx. 0.2cm 2 / g ~ approx. 1.5cm 3 / g, approx. 0.2cm 3 / g ~ approx. 1.4cm 3 / g, approx. 0.2cm 3 / g ~ approx. 1.3cm 3 / g, approx. 0.3cm 3 / g ~ approx. 1.2cm 3 / g, approx. 0.3cm 3 / g ~ approx. 1.cm 3 / g, approx. 0.4cm 3 / g ~ approx. 1.1cm 3 / g, or approximately 0.4cm 3 / g ~ approx. 1cm 3 The MOF extruded material may have a porosity of about 30% to about 100% of the raw MOF material, for example, about 50% to about 95%, or about 70% to about 90% (measured using ASTM D3663).
[0089] The MOF extruded material produced by this method may have an average pore size of approximately 1 Å to approximately 40 Å, for example, approximately 2 Å to approximately 25 Å, or approximately 6 Å to approximately 23 Å (measured using ASTM D4365). Purpose
[0090] MOF extrudes can be used in applications such as catalysis, separation, purification, and capture. For example, MOF extrudes can be brought into contact with gaseous feedstock to be processed in a reactor, whether it be a fixed-bed reactor, a radial reactor, a fluidized-bed reactor, or an absorption-bed reactor. When used in the fields of catalysis and separation, the expected ACS value is 0.9 daN / mm or higher, for example, 1 daN / mm or higher. Therefore, the described MOF extrudes have sufficient mechanical strength for use in the fields of catalysis and separation.
[0091] MOF extrudes can be used in processes where having porous materials or channels is advantageous over solids or powders. Specifically, these include catalysts, catalyst supports, adsorption, fluid storage, desiccants, ion exchange materials, molecular sieves (separators), chromatography materials, materials for selective molecular release and / or incorporation, molecular recognition, nanotubes, and nanoreactors.
[0092] In some embodiments of its application, MOF extrudes are used as catalysts in fixed-bed / packed-bed reactors. In principle, MOF extrudes may be used in gas-phase reactions or liquid-phase reactions, in which case the solid form is suspended in a slurry. Furthermore, MOF extrudes can be used as catalysts in a variety of reactions in which the presence of channels and / or pores incorporated therein is known or believed to enhance the activity and / or selectivity and / or yield of the reaction.
[0093] Furthermore, it is also applied to the storage of compounds, particularly gaseous compounds. The pore size and porosity of MOF extruders can enable excellent storage or sequestration of gaseous compounds such as CO2, CH4, or H2, which are of particular interest in the energy industry, as well as gas separation.
[0094] Features of the present invention are described in the following non-limiting embodiments. [Examples]
[0095] A metal-organic skeleton HKUST-1 (Cu3btc2, where btc is 1,3,5-benzenetricarboxylate) was used and prepared by marmixing water with one of the following liquid extrusion aids: alkyl alcohol (1-propanol, 1-butanol, or 1-hexanol). Ethanol was used as an alcohol additive for comparison.
[0096] 1-propanol was mixed with water and then added to the extrusion-type marmix (hereinafter referred to as MOF material). 1-butanol and 1-hexanol were added separately because they are not water-soluble. All experiments were conducted with a water-to-alcohol ratio of 1:1. All marmix was extruded in a ram extruder (commonly known as a high-temperature melt extruder (HTME)) with a solid content of 43%. P1, P2, and P3 are the pressures measured during extrusion: at the start, middle, and end of extrusion. The results of this experiment are shown in Table 1 below. This demonstrates that using long-chain alcohols as extrusion aids, specifically liquid extrusion aids, reduces the pressure during extrusion. [Table 1]
[0097] As shown in Table 1, the pressure decreased for all three types of alcohol compared to when ethanol was used, with 1-hexanol showing a particularly significant decrease. It appears that the long carbon chains of long alcohols provide more lubrication during the extrusion process, resulting in such low pressure.
[0098] Figure 1 shows the retention of crystallinity of MOFs, HKUST-1, extruded using each long-chain alcohol, and Figure 2 shows the N2 adsorption isotherms used to determine the BET surface area of each extruded material.
[0099] Furthermore, using graphite as an extrusion aid allowed for a further reduction in extrusion pressure. Similar to long-chain alcohols, it is a solid extrusion aid that can lower extrusion pressure. Specifically, experiments were conducted to use graphite (less than 20 μm) as a lubricant when pelletizing it, by pressing pellets with 2% and 20% graphite at 500 psi and 1000 psi, respectively. The resulting surface area was compared with the surface area of HKUST-1 powder, and weighting was applied to account for the insufficient surface area of graphite. When mixed, the graphite appeared to coat the outer surface of the HKUST-1 particles. A comparison of BET surface areas is shown in Table 2 below. [Table 2]
[0100] In Table 2, the percentage of graphite is expressed as a weight percentage relative to the total weight of solids. For example, 2% graphite by weight means that 2% of the solids are graphite and 98% of the solids are HKUST-1 powder or MOF material.
[0101] Based on the success of the pelletization experiment, HKUST-1 was extruded with graphite, and the pressure change was observed as a function of the amount of graphite (GJM-2016-33584, MTK-026). The sample was extruded through a 1 / 16" (inch) cylinder die of an HTME hand press. A 2% graphite sample did not reduce the extrusion pressure and retained most of the surface area of HKUST-1. Including 20% graphite significantly reduced the pressure, and it was also significantly lower than the pressure required for the same solid content without graphite (GJM-2016-33396, MTK-017). Furthermore, the surface area with weight considering graphite was 1327 m². 2 The weight of the graphite per gram retains 94% of the surface area, indicating that the graphite does not clog the pores of the HKUST-1 material. By using 20% or less of graphite, the pressure inside the extruder can be reduced while maintaining the properties of the metal-organic skeleton in the extruded product.
[0102] Polyvinyl alcohol (PVA) was also tested as an extrusion aid. Both ZIF-8 and HKUST-1 used PVA as a polymer extrusion aid. It was shown that adding a small amount of polyvinyl alcohol to polyvinyl acetate as a binder improved crush strength. For example, the crush strength of HKUST-1 improved from 53 wt lbs / in to 213 wt lbs / in with the addition of 2 wt% polyvinyl alcohol, and it was confirmed that the surface area was also significantly maintained compared to the case without polyvinyl alcohol. Table 4 shows the crush strength and BET surface area of these two metal-organic skeletons (PVA: polyvinyl alcohol, PVAc / DI: polyvinyl acetate / deionized water (w / w)). The crush strength of the MOF extruders was measured in accordance with ASTM D7084 using a Varian VK200. The BET surface area was measured in accordance with ASTM D3663. [Table 3]
[0103] Extrusion using polyvinyl alcohol (PVA) exhibits significantly higher crush strength compared to extrusion without PVA. As an extrusion aid, PVA can improve both crush strength and mechanical stability. Furthermore, as demonstrated with various extrusion aids and different MOF materials having different metal nodes, pore sizes, and crystal structures, the inclusion of extrusion aids does not negatively affect the crystallinity and surface area of the MOF material. This disclosure provides different types of extrusion aids for MOF materials. Each extrusion aid shares the common characteristic of enabling extrusion molding while maintaining the quality and porosity of the MOF material, and producing MOF extruded products of sufficient quality for industrial applications. For certain MOFs, it is necessary to extrude with a mixture of water and ethanol to mitigate the degradation of the MOF due to adsorption heat when exposed to liquid water. As described above, replacing ethanol with a long-chain alcohol provides a similar effect to ethanol while suppressing the pressure increase during extrusion molding. In the extrusion molding of MOF materials, reduced pressure is crucial to maintain the crystallinity and porosity of the MOF under high pressure. Furthermore, large screw extruders used for the large-scale production of catalyst extruders have pressure limitations, requiring a reduction in the extrusion pressure.
[0104] As mentioned above, metal-organic skeleton extrusion is a relatively unexplored field, but it is a field necessary for formulating these new materials for use in various applications. Because MOFs have low rigidity, they can be damaged by the high pressure and high temperature they are subjected to during extrusion. Furthermore, binders are often required to improve the mechanical strength of the resulting extruded material. However, many binders are incompatible with MOFs, mainly due to the lack of compatible surfaces. Therefore, this specification provides a method for producing MOF extruded materials using different extrusion aids that reduce pressure during extrusion, while maintaining the structural integrity of the MOF material and improving the mechanical strength of the MOF extruded material. Interestingly, the improvement in reduced pressure can be achieved by using both solvents that do not remain in the final extruded material and solid extrusion aids that do remain in the final extruded material. The use of extrusion aids enables novel approaches not previously possible.
Claims
1. mixing the metal-organic framework material with an extrusion aid to form a metal-organic framework extrusion mixture; and extruding the metal-organic framework extrudate mixture through an extruder to produce metal-organic framework extrudates; 1. A method for producing metal-organic framework extrudates in an extruder, comprising: reducing the pressure in the extruder by 10% to 55% compared to the pressure in the extruder when extruding the metal-organic framework without the extrusion aid; the extrusion aid is a polymeric extrusion aid comprising polyvinyl alcohol and polyvinyl ester; A method for producing metal-organic framework extrudates, wherein the pressure in the extruder using an extrusion aid is between 0.1 MPa and 20 MPa.
2. 10. The method of claim 1, wherein the extruded metal-organic framework mixture comprises 0.5% to 10% by weight of polyvinyl alcohol.
3. 3. The method of claim 1 or 2, wherein the metal-organic framework extrusion mixture comprises polyvinyl acetate and water, and the ratio of polyvinyl acetate to water is from 1:1 to 1:
3.
4. The method according to any one of claims 1 to 3, wherein the metal-organic framework extrudates are shaped as rods, ribbed rods, tablets, rings, annular tablets, spheres, pellets, honeycomb bodies, or granules.
5. Metal-organic framework materials include HKUST-1, UiO-66, ZIF-8, ZIF-7, MIL-100, MOF-74, M 2 (m-dobdc), MOF-274, Cu(Qc) 2 and combinations thereof.
6. 6. The method of any one of claims 1 to 5, wherein the metal-organic framework extrudate has a comparative BET surface area of from 40% to 100% relative to the raw metal-organic framework prior to extrusion.
7. 7. The method of any one of claims 1 to 6, further comprising the step of ageing the metal-organic framework extrudates at a temperature between 40°C and 150°C for a period of at least 30 minutes and / or calcining the metal-organic framework extrudates at a temperature between 100°C and 300°C for at least 1 hour.
8. The method according to any one of claims 1 to 7, wherein the step of extruding the metal-organic framework extrusion mixture is carried out through a die having a diameter of from 0.01 mm to 50 mm.
9. The method of any one of claims 1 to 8, further comprising washing the metal-organic framework extrudates with a solvent.
10. 10. The method of claim 9, wherein the solvent is selected from the group consisting of water, methanol, ethanol, dimethylformamide, acetone, diethyl ether, acetonitrile, ketones, amides, esters, ethers, nitriles, aromatic hydrocarbons, aliphatic hydrocarbons, and combinations thereof.
11. 11. The method of any one of claims 1 to 10, wherein the extruded metal-organic framework mixture comprises 20 wt% to 70 wt% solids, based on the total weight of the extruded metal-organic framework mixture.
